IMPLEMENTATION OF MARKET DAY ACTIVITIES IN GROWING ENTREPRENEURIAL CHARACTER FOR MIN 3 GUNUNGKIDUL STUDENTS - Hartati, Sri; Anwar, Khoirul; Musidah, Siti; Nurhuda, Abid (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2023)
Entrepreneurial character building can be developed in children from elementary school. This study intends to describe how to implement market activities at MIN 3 Gunungkidul and how to grow entrepreneurial character values for students. The growth of this entrepreneurial character is carried out to realize the vision of MIN 3 Gunungkidul, in creating skilled students, and realizing the mission of "Instilling an entrepreneurial spirit so that they are skilled and independent". The author uses a qualitative research method, with the case study method. The setting for the implementation of this research took place at MIN 3 Gunungkidul, in December 2022. All madrasah residents, consisting of teachers, the market day committee, students, parents, and school principals were the research subjects. In collecting data, researchers used direct observation techniques (observation), interviews, and documentation. The results of this study indicate that the market day activities held at the end of this odd semester are a place for students to learn entrepreneurial character from a young age and provide provisions for students to become entrepreneurs who are brave and confident in facing various challenges in the future.